Paraspinal arteriovenous fistula with perimedullary venous drainage. - Cognard, C; Semaan, H; Bakchine, S; Miaux, Y; Thibault, S; Sola Martinez, M T; Chiras, J (American Journal of Neuroradiology, 1995)
A paravertebral presacral posttraumatic arteriovenous fistula drained through the ascending lumbar vein to the epidural plexuses and perimedullary veins. The patient did not have symptoms of myelopathy, only low-back pain and radicular hypoesthesia. The lesion was embolized with a large balloon and clinical symptoms disappeared.